"The Future of Vulvar Disease: New and Ongoing Challenges". Issue 2 (April 2018) - Marchitelli, Claudia
Abstract : Abstract: The 21st century brought along a number of discoveries and medical advances. With the advances, we can mention the following: target therapies for cancer, genomics and molecular biology, pharmacogenomics, minimally invasive and robotic surgery, immunosuppressive therapies in transplant patients, human papillomavirus in the era of vaccination, and aesthetic vulvovaginal procedures. All of them have greatly influenced medicine. As a scientific society, we have several challenges. In the past, you had to go to a library to get information. Now, we have readily available, accessible information. Thus, here comes the debate; we are facing a change in our educational paradigm, which needs to be approached from an integral and holistic perspective. New historical and cultural circumstances call for a deep reflection on the current social validity of scientific societies. They should be open to new ideas and allow dissent, work in teams, and speak a common language. They must be organized and, in constant communication with its members, support and organize research developing well-designed clinical trials and observational studies. We should work for our patients, recognizing the importance of the whole woman. We all have a great scientific and humanitarian challenge; to succeed, we must not lose sight of who we are working for. We work for them, our patients, and not for us . Our mission is to take care of our them!